The Effect of Key Audit Matters on The Behavior of Accepting Audit Service Fees in Indonesia - Alit Triani, Ni Nyoman; Dody Setyawan, Made; Bhilawa, Logar; Prasetyo, Eko; Abie, Noviara (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of the research is to examine the effect of implementing the new ISA 701 regulation, namely communicating the most significant risks in the audit process of an entity's financial statements or known as key audit matters, especially for entities listed on the Indonesian capital market, on changes in audit fee acceptance behavior. This study provides evidence that the greater the audit effort undertaken has an impact on audit fee receipts, as well as its effect on the size of the public accounting firm. This study uses a cross section of 720 data sourced from the publication of the audit results of the 2022 financial statements of companies going public. The test method uses multiple regression to analyze the results by disaggregating the number of KAM paragraphs of less than 2 and more than 2 paragraphs, using disaggregation of audit tenure of less than two years and more than 2 years and disaggregation of company age of less than 19 years and more than 19 years. The study results show that key audit matters and audit firm size have a positive effect on all tests